The Reach of Depression Screening Preceding Treatment: Are There Patterns of Patients' Self-Selection? - Dea Ajduković; Mirjana Pibernik-Okanović; Mario Šekerija; Norbert Hermanns (International Journal of Endocrinology)
This study evaluated the reach of depression screening followed by treatment programs for subsyndromal depression and explored demographic and clinical characteristics of patients who were reached versus those who were not. A two-item Patient Health Questionnaire-Depression was sent to 4196 type 2 diabetic patients. Positively screened patients were interviewed to assess the severity of depression, and those with subclinical symptoms were invited to treatment groups. The reach of screening procedure was evaluated by the total response rate, proportion of positive depression screenings, and proportion of eligible patients entering treatment programs. Predictors of responsiveness to screening and of participation in treatment were determined using logistic regression. Of the 34% of patients who returned the questionnaire (n=1442), 40% reported depressive symptoms and a need for professional help (n=581). Age (OR = 1.06, 95% CI = 1.05–1.08), BMI (OR = 1.02, 95% CI = 1.00–1.04), HbA1C (OR = .92, 95% CI = .86–.99), and LDL-cholesterol (OR = .90, 95% CI = .81–1.00) correlated with response to screening. Willingness to accept treatment was predicted by professional status (OR = 3.24, 95% CI = 1.53–6.87), education (OR = 1.21, 95% CI = 1.05–1.38), and BMI (OR = .91, 95% CI = .85–.98). Older patients with better diabetes control were more likely to be reached by postal screening for depressive symptoms. Professionally inactive, better-educated persons and those with lower BMI were more likely to participate in the intervention for subsyndromal depression.